Pengembangan Media Video Pembelajaran pada Mata Pelajaran Sejarah Kebudayaan Islam untuk Siswa Kelas VII MTSN (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to produce learning video media for SKI Class VII MTsN subjects that are valid and practical. This type of research is development research, known as Research and Development (R&D), using the 4-D development model. The development procedure in this research consists of 4 stages, namely, (1) Define, (2) Design, (3) Develop, (4) Disseminate. The product validity test was carried out by 3 validators, namely 1 material validator and 2 media validators. Product trials were carried out on class VII students at MTsN 5 Tanah Datar with the aim of finding out the practicality of the product being developed. The results of material validation by material expert validators obtained an average of 4.94 in the "very valid" category. The results of the media validator assessment with validator I obtained an average of 4.93 in the "very valid" category and the validation results with validator II obtained an average of 4.93 in the "very valid" category. This learning multimedia is said to be practical based on the results of the practicality test with an average of 4.5. Based on the results of the validity test and practicality test, it can be concluded that learning multimedia in PAI subjects for class IV elementary school is suitable for use in learning